MANAGEMENT OF NATURAL RESOURCES WITH AIM SUSTAINABLE RURAL DEVELOPMENT: COMPARATIVE ANALYSIS OF THE CASE OF THE LITHUANIAN ELDERSHIP AND POLISH MUNICIPALITY (Polityki Europejskie, Finanse i Marketing)
The article analyzes sustainable rural development as development of rural localities that promotes progressive and effective management of resources, in coordination of their protection and sustainable usage with regard to requirements set in different areas (economics, social development, culture, law and environmental protection). The natural resources’ sorts, functions and indicators related to usage of natural resources are described. The strengths and weaknesses of environmental changes, the solution possibilities of the sorest problems and probable threats are named. The essential attention is given to the main components of the environment – air, water, climate, landscape, and problems of biological diversity. The article stresses the sustainable development of natural resources through strategic usage of natural resources that is beneficial to rural localities and residents. The described research was carried out in Zasliai eldership of Kaisiadorys region (Lithuania) and in Siedlce Municipality of Siedlce Poviat (Poland). The condition of its natural resources, management tools and significance for sustainable development of the locality were assessed. The improvement directions of management of natural resources in the eldership were named and substantiated with regard to the components of sustainable development (economic, environmental protection and social-cultural).